Answer:
(ab - 6)(2ab + 5)
Step-by-step explanation:
Assuming you require the expression factorised.
2a²b² - 7ab - 30
Consider the factors of the product of the coefficient of the a²b² term and the constant term which sum to give the coefficient of the ab- term
product = 2 × - 30 = - 60 and sum = - 7
The factors are - 12 and + 5
Use these factors to split the ab- term
= 2a²b² - 12ab + 5ab - 30 ( factor the first/second and third/fourth terms )
= 2ab(ab - 6) + 5(ab - 6) ← factor out (ab - 6) from each term
= (ab - 6)(2ab + 5) ← in factored form
Answer:
= - 21 + 6x² + 1
Step-by-step explanation:
Differentiate each term using the power rule
(a ) = na
Given
y = - 3 + 2x³ + x , then
= (7 × - 3 ) + (3 × 2)x² + (1 × 1 )
= - 21 + 6x² + 1
Markup = $4
b) markup as a percentage of cost is 33.3%
Step-by-step explanation:
Markup
markup = selling price - cost
= $13 - 9
... markup = $3
Markup as a Percentage of Cost
To find the percent markup, divide the markup by the reference value and multiply the ratio by 100%. The reference value for markup is usually cost price, but sometimes may be selling price.
... markup / cost × 100% = 3/9×100% = 33 1/3% ≈ 33.3%
DEF= 6 ft^2
A= 1/2*b*h
Plug in what you know.
6= 1/2*4*h
Multiply like terms.
6=2*h
Divide 2 on both sides.
3=h
If the base of ABC= 12
12/4=3
3*3=9
A= 1/2*b*h
A= 1/2*12*9
A= 1/2*84
A= 42
The area of ABC is 42 ft^2
I hope this helps!
~kaikers